The Role of Cyclic Nucleotides in the Release of Tissue-Type Plasminogen Activator and von Willebrand Factor - Tranquille, N; Emeis, J J (Thrombosis and Haemostasis, 1993)
The modulation of the induced acute release of tissue-type plasminogen activator (t-PA) and of von Willebrand factor (vWF) by compounds affecting cyclic nucleotide levels was studied, using an isolated rat hindleg perfusion system. Platelet-activating factor (PAF; 5 nM) or bradykinin (0.8 (μM) were used to induce release of t-PA and vWF.The guanylate cyclase activators sodium nitroprusside and atrial natriuretic factor reduced the induced release of t-PA and vWF. Release was not affected by inhibiting nitric oxide production with NG-nitro-L-arginine. The effects of nitroprusside and atrial natriuretic factor could not be reproduced by infusion of 8-bromo-cGMP.The adenylate cyclase activator forskolin had no effect on bradykinin-induced release of t-PA and vWF, reduced PAF-induced t-PA release, but potentiated PAF-induced vWF release. These modulatory effects were only partially mimicked by infusion of 8-bromo-cAMP.None of the compounds tested was able to induce the release of t-PA or of vWF in the absence of stimulation by bradykinin or platelet-activating factor. Cyclic nucleotides can thus modulate, but not induce, the acute release of t-PA and vWF from perfused rat hindlegs.